Análise e aplicabilidade do corante composto por antocianinas do fruto do açaí (Euterpe oleracea) em cromovitrectomia em humanos - Caiado, Rafael Ramos [UNIFESP] (2019)
Purpose: This study aimed to analyze the anthocyanin content and test the applicability of a novel dye extracted from the acai fruit (Euterpe oleracea) in chromovitrectomy in humans. Methods: Ophthalmos Pharmaceutical Industry S/A (São Paulo, Brazil) developed three concentrations of the acai dye (10%, 25% and 35%) equivalent to 100, 250 and 350 mg of lyophilized acai pulp samples that were diluted in 1 ml of phosphate buffer solution (pH 7 and 300 mOsm). In the first study, the lyophilized acai pulp samples were analyzed by high-performance liquid chromatography (HPLC) using cyaniding 3-O-glucoside, hemoorientin, and orientin and mass spectrometry (MS) to identify and compare color dye distinctions. Mass spectrometry was used to identify and compare the dye concentrations for five isolated basic anthocyanin molecules. In study 2 rabbits were injected intravitreously with 10%, 25% and 35% concentrations of the acai dye. Control eyes received balanced salt solution (BSS). Electroretinogram (ERG), fundus imaging, fluorescein angiography (FA), optical coherence tomography (OCT), light and transmission microscopy (LM/MET) were performed. In study 3 the ethics committee of the Federal University of São Paulo and the National Council of Research (CONEP) approved the study protocol of a phase I/II clinical trial in 25 human eyes. Inclusion criteria: Patients diagnosed with idiopathic macular hole, of both genders, older than 18 years. Exclusion criteria: previous glaucoma, active uveitis, ocular conditions other than macular holes that could affect or limit the postoperative results and previous ocular surgeries other than uncomplicated cataract. Surgical technique: twenty-three-gauge four-port PPV + phacoemulsification (if phakic eyes) followed by both posterior hyaloid detachment and ILM peeling guided by 25% acai fruit dye staining as well as perfluoropropane injection and 5 day prone positioning. A questionnaire about the ability of the dye to stain the posterior hyaloid and ILM was given to the 10 surgeons that performed the 25 surgeries immediately after the procedures. Dye toxicity was analyzed by anatomic and functional examinations before surgery and at days 1, 30 and 180. The anatomic analysis of tested eyes included best-corrected visual acuity, tonometry, biomicroscopy, fundoscopy, fundus imaging, FA, OCT and optical coherence tomography angiography. Functional analysis was performed by ERG. Student’s t test and Analysis of Variance (ANOVA), with repeated measures, was used and p-values <0.05 were significant. Results: Study 1 showed the presence of five different anthocyanin molecules in all three concentrations of the acai dye: cyanidin-3- 0-glucoside > homoorientin > orientin > taxifolin > isovitexin. In study 2, using a rabbit model, fundus imaging showed increased vitreous opacity with increased dye concentrations. FA and OCT showed normality in all concentrations. Comparison between BSS and dye concentrations were analyzed using Kruskal-Wallis and Mood’s median test (p <0.05). At 24h, ERGs showed reduced amplitudes from baseline in all eyes. Median b-wave amplitudes nonsignificantly decreased and latency increased with 10% and 25%; findings were significant (p <0.05) for 35%. LM and TEM showed no abnormalities for 10% and 25%. With 35%, TEM showed ganglion cell edema at 24 h that resolved after 7 days. Vacuolization, multilamellar bodies, and nerve bundle damage occurred at 24 h/7 days in the inner nuclear layer. Mitochondrial cristae disruption occurred in the inner photoreceptor segment at 24 h that decreased by 7 days. In Study 3 (clinical trial in humans) showed no abnormalities after both anatomical and functional analysis independent on the tested times. The anatomical outcomes showed a closure rate of 19 out of 25 operated eyes. All surgeons reported that the acai fruit dye at a 25% concentration stained the posterior hyaloid detachment and the ILM with a purple color. Conclusions: The acai dye extracted from the acai fruit is mainly composed of the anthocyanin cyanidin-3-0-glucoside. The acai dye in the concentrations of 10% and 25% were safe in rabbits. Six months results of a phase I/II trial showed that the new dye based on the anthocyanins from the acai fruit in a 25% concentration was safe and useful for identifying both posterior hyaloid and ILM during vitreoretinal surgery in humans. This purple dye may be an alternative to chromovitrectomy and additional studies are necessary.